YOU USE 1 7/8
<span>red paint and blue paint</span>
Answer:
The euation of the linear function is:
Step-by-step explanation:
As the function has the values
Thus, the two points are:
Finding the slope between (5, -1) and (0, -1)
![\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSlope%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![\left(x_1,\:y_1\right)=\left(5,\:-1\right),\:\left(x_2,\:y_2\right)=\left(0,\:-1\right)](https://tex.z-dn.net/?f=%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%3D%5Cleft%285%2C%5C%3A-1%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3D%5Cleft%280%2C%5C%3A-1%5Cright%29)
![m=\frac{-1-\left(-1\right)}{0-5}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-1-%5Cleft%28-1%5Cright%29%7D%7B0-5%7D)
![m=0](https://tex.z-dn.net/?f=m%3D0)
We know that the slope-intercept form of the line equation is
y=mx+b
where m is the slope and b is the y-intercept
We also know that the y-intercept can be computed by setting x=0 and finding the corresponding value of y.
so at x = 0, y = -1
Thus, the y-intercept 'b' = -1
Now, substituting m = 0 and b = -1 in the slope-intercept form of the line equation
y = mx+b
y = 0x + -1
y = -1
Therefore, the euation of the linear function is:
Answer:
Quartz, Cups
Step-by-step explanation:
1 gallon = 16 cups
1 quartz = 4 cups
1 pint = 2 cups
1 fluid ounce = 1/8 cups
By algebra properties we find the following relationships between each pair of algebraic expressions:
- First equation: Case 4
- Second equation: Case 1
- Third equation: Case 2
- Fourth equation: Case 5
- Fifth equation: Case 3
<h3>How to determine pairs of equivalent equations</h3>
In this we must determine the equivalent algebraic expression related to given expressions, this can be done by applying algebra properties on equations from the second column until equivalent expression is found. Now we proceed to find for each case:
First equation
(7 - 2 · x) + (3 · x - 11)
(7 - 11) + (- 2 · x + 3 · x)
- 4 + (- 2 + 3) · x
- 4 + (1) · x
- 4 + (5 - 4) · x
- 4 - 4 · x + 5 · x
- 4 · (x + 1) + 5 · x → Case 4
Second equation
- 7 + 6 · x - 4 · x + 3
(6 · x - 4 · x) + (- 7 + 3)
(6 - 4) · x - 4
2 · x - 4
2 · (x - 2) → Case 1
Third equation
9 · x - 2 · (3 · x - 3)
9 · x - 6 · x + 6
3 · x + 6
(2 + 1) · x + (14 - 8)
[1 - (- 2)] · x + (14 - 8)
(x + 14) - (8 - 2 · x) → Case 2
Fourth equation
- 3 · x + 6 + 4 · x
x + 6
(5 - 4) · x + (7 - 1)
(7 + 5 · x) + (- 4 · x - 1) → Case 5
Fifth equation
- 2 · x + 9 + 5 · x + 6
3 · x + 15
3 · (x + 5) → Case 3
To learn more on algebraic equations: brainly.com/question/24875240
#SPJ1
Answer: you unsubscribe from it
Step-by-step explanation: